RNA-Seq methods for transcriptome analysis - Hrdlickova, Radmila; Toloue, Masoud; Tian, Bin (Wiley interdisciplinary reviews. RNA, 2017)
Deep sequencing has been revolutionizing biology and medicine in recent years, providing single base-level precision for our understanding of nucleic acid sequences in high throughput fashion. Sequencing of RNA, or RNA-Seq, is now a common method to analyze gene expression and to uncover novel RNA species. Aspects of RNA biogenesis and metabolism can be interrogated with specialized methods for cDNA library preparation. In this study, we review current RNA-Seq methods for general analysis of gene expression and several specific applications, including isoform and gene fusion detection, digital gene expression profiling, targeted sequencing and single-cell analysis. In addition, we discuss approaches to examine aspects of RNA in the cell, technical challenges of existing RNA-Seq methods, and future directions. WIREs RNA 2017, 8:e1364. doi: 10.1002/wrna.1364 For further resources related to this article, please visit the WIREs website.